The influence of the problem solving learning model on students' self-confidence and learning outcomes in mathematics learning - Zahara Febriyanti Pasaribu; Tasnim Rahmat; Iltavia Iltavia; Uqwatul Alma Wizsa (Polyhedron International Journal in Mathematics Education, 2026)
This study was motivated by the low mathematics learning outcomes and self-confidence of eleventh grade students. Most students have not reached the minimum completion limit of 75. In addition, the learning process is still teacher-centered so that students tend to feel bored, lack focus, and lack confidence in solving mathematical problems. This study aims to determine the effect of the Problem-Solving learning model on self-confidence and mathematics learning outcomes. The design of this study is a static group comparison design. Participants were selected using a random sampling technique, with class XI F2 as the control class and class XI F3 as the experimental class. The research instruments used were a self-confidence questionnaire and a mathematics learning outcome test. Data were analyzed using a t-test with the help of SPSS software at a significance level of 0.05. The results showed that the Problem-Solving learning model had a significant effect on students’ self-confidence, as indicated by a significance value of 0.004 <0.05. In addition, the Problem-Solving learning model also had a significant effect on students’ mathematics learning outcomes with a significance value of 0.015 <0.05. Thus, it can be concluded that the application of the Problem-Solving learning model is able to improve self-confidence and mathematics learning outcomes. As a recommendation, the Problem-Solving learning approach is suggested as one of the strategic choices in mathematics education to increase students’ self-confidence and learning achievements, and can be considered for application to various materials and different levels of education.